Quantitative seismic characterization for gas hydrate- and free gas-bearing sediments in the Shenhu area, South China sea. (May 2022) - Qian, Jin; Kang, Dongju; Jin, Jiapeng; Lin, Lin; Guo, Yiqun; Meng, Mianmo; Wang, Zhaoqi; Wang, Xiujuan
Abstract: During China's first gas hydrate drilling expedition, a gas hydrate-bearing layer (GHBL) of ≈25 m thickness was identified above a bottom-simulating reflection (BSR) at site SH2 in the Shenhu area, South China Sea. This study considers the GHBL and the underlying free gas-bearing layer (FGBL) as a whole and evaluates them using quantitative seismic characterization. The reprocessed seismic data, correlated to well log data, reveal the BSR to be accompanied by newly-identified reflections of positive polarity from the top of the GHBL and the base of the FGBL. Of note are phase reversals along individual reflections that cross the top of the GHBL and the base of the FGBL. Phase reversals at the top of the GHBL are a previously little known seismic feature, and seismic forward modeling shows them to provide a direct indicator for the presence of gas hydrate. Amplitude versus offset (AVO) analysis indicates that the two new reflections have characteristics distinct from those of the BSR. Gas hydrate and free gas saturations derived by AVO analysis and seismic impedance inversion, respectively, are consistent with values estimated from sonic velocities, chloride anomalies and pressure cores. The saturations calculated from acoustic impedance inversion show that both gas hydrate and free gas of high saturation are discontinuous, and that free gas has a clear stratified distribution. The distribution of gas hydrate is generally consistent with that of free gas below the BSR, indicating that gas hydrate near site SH2 is mainly controlled by free gas in the underlying FGBL. The quantitative interpretation presented in this study provides a new and reliable method for the characterization of gas hydrate-bearing sediments in areas with no wells, and for the pre-drilling assessment of free gas hazard. Graphical abstract: Image 1 Highlights: Two normal polarity reflections associated with phase reversals in cross-cutting reflections are identified at the top of a gas hydrate-bearing layer (GHBL) and the base of a free gas-bearing layer (FGBL). AVO characteristics and polarities of reflections from the top of the GHBL and the base of the FGBL are shown to be distinct from those of the BSR. AVO analysis is extended to derive gas hydrate saturation at the top of the GHBL and free gas saturation at the base of the FGBL. Gas hydrate and free gas are uniformly distributed at pore scale but areas of high saturation are discontinuous at seismic scale.